Performing indigenous identities on the contemporary Australian stage : land, people, culture - Thurow, Susanne Julia (2019)
"Over the past 50 years, Indigenous Australian theatre practice has emerged as a dynamic site for the discursive reflection of culture and tradition as well as colonial legacies, leveraging the power of storytelling to create and advocate contemporary fluid conceptions of Indigeneity. Performing Indigenous Identities on the Contemporary Australian Stage offers a window into the history and diversity of this vigorous practice. It introduces the reader to cornerstones of Indigenous Australian cultural frameworks and on this backdrop discusses a wealth of plays in light of their responses to contemporary Australian identity politics. The in-depth readings of two landmark theatre productions, Scott Rankin's Namatjira (2010) and Wesley Enoch & Anita Heiss' I Am Eora (2012), trace the artists' engagement with questions of community consolidation and national reconciliation, carefully considering the implications of their propositions for identity work arising from the translation of traditional ontologies into contemporary orientations. The analyses of the dramatic texts are incrementally enriched by a dense reflection of the production and reception contexts of the plays, providing an expanded framework for the critical consideration of contemporary postcolonial theatre practice that allows for a well-founded appreciation of the strengths yet also pointing to the limitations of current representative approaches on the Australian mainstage. This study will be of great interest to students and scholars of Postcolonial, Literary, Performance and Theatre Studies"--